2016
DOI: 10.1039/c6ra15051a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring saccharinate-tetrazoles as selective Cu(ii) ligands: structure, magnetic properties and cytotoxicity of copper(ii) complexes based on 5-(3-aminosaccharyl)-tetrazoles

Abstract: Saccharinate-tetrazolesTSand2MTSbind selectively to copper(ii). The resulting copper complexes have shown a huge increase in thein vitrocytotoxicity against hepatic carcinoma cells (HepG2) compared to the corresponding nontoxic free ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…The synthesis of 3-((5-(trifluoromethyl)-1,3,4-thiadiazol-2-yl)amino)benzo[ d ]isothiazole 1,1-dioxide (AL14) was conducted by adapting the methodology developed by Ismael et al [ 17 , 28 ] ( Scheme 1 ). AL14 was synthesized by coupling 2-amino-5-trifluoromethyl-1,3,4-thiadiazole 3 with pseudo -saccharyl chloride 2 , which was previously prepared from commercially available saccharin 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of 3-((5-(trifluoromethyl)-1,3,4-thiadiazol-2-yl)amino)benzo[ d ]isothiazole 1,1-dioxide (AL14) was conducted by adapting the methodology developed by Ismael et al [ 17 , 28 ] ( Scheme 1 ). AL14 was synthesized by coupling 2-amino-5-trifluoromethyl-1,3,4-thiadiazole 3 with pseudo -saccharyl chloride 2 , which was previously prepared from commercially available saccharin 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The metal chelating activities were evaluated by spectrophotometry, using selective chelating indicators that produce coloured complexes, following methods described in the literature for Cu(II) and Fe(II) [ 31 ] and adopting the method described by Ahmed and Chowdhury [ 32 ] for Cd(II), with some adjustments for 96-well plates. Thus, the metal ion chelating activities were determined by measuring the colour changes due to the Cd(II)/5,7-dibromo-8-hydroxyquinoline (DBHQ) complex (at 396 nm) [ 32 ], Cu(II)/pyrocatechol violet (PV) complex (at 632 nm), and Fe(II)/ferrozine complex (at 562 nm) [ 17 ]. The capacity of the tested compound to chelate the metals should be reflected in a decrease in absorbance at each corresponding wavelength.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently developed saccharinate‐based molecules where the saccharyl system is linked to a tetrazolyl moiety ( 1 ; Scheme ; R=tetrazolyl), studied their structure and properties and uncovered their potential as multidentate nitrogen ligands in coordination chemistry. Interestingly, it was found that some of the N ‐linked tetrazole‐saccharinates investigated act readily as selective Cu II chelators, over Fe II and Ca II . The chelators and corresponding copper complexes were scrutinized regarding their toxicity towards various cancer cell lines and also towards non‐tumoral cells.…”
Section: Introductionmentioning
confidence: 99%
“…The chelators and corresponding copper complexes were scrutinized regarding their toxicity towards various cancer cell lines and also towards non‐tumoral cells. Quite surprisingly, the ligands did not show toxicity but the corresponding copper complexes revealed high toxicity towards all tumor cell lines tested, with IC 50 values at the low micromolar range of concentrations . From these preliminary results we selected one compound, 2‐methyltetrazole saccharinate, for deeper investigations of anti‐proliferative activity, analysis of cell cycle distribution, apoptosis induction, and oxidative stress levels.…”
Section: Introductionmentioning
confidence: 99%